The Concept of Islamic Education in the Perspective of the Qur'an and Hadith - Amin Yusdian Faishol; Ardiansyah Kusmawan; Fajar Saripudin; Samsul Pajri; Yayat Hidayat (CV Projurnal Mitra Publikasi, 2025)
This study aims to explore the concept of Islamic education from the perspective of the Qur'an and Hadith. Islamic education is known as education that is not only oriented towards intellectual development, but also forms character based on Islamic values. This study uses a qualitative method with a library research approach, analyzing the main sources, namely the Qur'an and Hadith, as well as other related references. The results of the study show that the Qur'an and Hadith provide a comprehensive foundation for Islamic education, including education in monotheism, morals, manners, and the importance of knowledge. Concepts such as ta'lim (teaching), ta'dib (education in manners), and tarbiyah (education in universal values) play an important role in building humans who are balanced intellectually, spiritually, and morally. In addition, education through example, as exemplified by the Prophet Muhammad SAW, is an effective method in forming noble morals.